En breve : cuentos de escritoras españolas (1975-2010) : estudios y antología - Encinar, Angeles; Valcárcel, Carmen (Colección Estudios críticos de literatura ;, 2012)
This volume contains fifteen essays by professors and researchers (Spanish, European and American) about the stories of Spanish authors published since 1975. The stories are discussed from various perspectives and different technical and thematic approaches. Also included is an anthology of short stories, one from each of the writers studied.--Publisher description.